Peptidoglycan Synthesis Machinery in Agrobacterium tumefaciens During Unipolar Growth and Cell Division - Cameron, Todd A. (American Society of Microbiology, 2014)
The synthesis of peptidoglycan (PG) in bacteria is a crucial process controlling cell shape and vitality. In contrast to bacteria such as Escherichia coli that grow by dispersed lateral insertion of PG, little is known of the processes that direct polar PG synthesis in other bacteria such as the Rhizobiales. To better understand polar growth in the Rhizobiales Agrobacterium tumefaciens, we first surveyed its genome to identify homologs of (~70) well-known PG synthesis components. Since most of the canonical cell elongation components are absent from A. tumefaciens, we made fluorescent protein fusions to other putative PG synthesis components to assay their subcellular localization patterns. The cell division scaffolds FtsZ and FtsA, PBP1a, and a Rhizobiales- and Rhodobacterales-specific l,d-transpeptidase (LDT) all associate with the elongating cell pole. All four proteins also localize to the septum during cell division. Examination of the dimensions of growing cells revealed that new cell compartments gradually increase in width as they grow in length. This increase in cell width is coincident with an expanded region of LDT-mediated PG synthesis activity, as measured directly through incorporation of exogenous d-amino acids. Thus, unipolar growth in the Rhizobiales is surprisingly dynamic and represents a significant departure from the canonical growth mechanism of E. coli and other well-studied bacilli.